KECEMASAN DAN OPTIMISME MASYARAKAT KOTA SURABAYA DALAM MENGHADAPI WABAH COVID-19 - Bergitha Dhei; Resy Mardiyanti (PSIKOWIPA (Psikologi Wijaya Putra), 2020)
This research aims to find out if there is a link between anxiety and optimism of the people of Surabaya in the face of the Covid-19 outbreak. Covid-19 pandemic is not finished until now, cases every day are increasing which causes anxiety in the community. Covid-19 is considered an unpleasant situation and conditions and can affect one's optimism to be able to cope with the condition. This research was conducted online to all surabaya people using purposive sampling with criteria: aged 18 years and above, male gender and downsizing and settled in Surabaya during the Covid-19 pandemic.The number of research samples as many as 400 people. The data collection tool in the form of an anxiety questionnaire consists of 37 points and optimism of 10 items using the Revised Test Life Orientation Scale (LOT-R). Data analysis is performed with simple non linear regression statistical techniques with the help of the SPSS 21.00 for Windows program. From the data analysis obtained the t count value is -1,984 with a sig value. value of 0.040 < 0.05. This indicates a negative link between anxiety and optimism. This means that the higher the anxiety, the lower the optimism of the people of Surabaya in the face of Covid-19 and the lower the anxiety, the higher the optimism of the people of Surabaya in the face of Covid-19.